Examining Organisational Culture with OCAI among Technical Management BSc Students of the University of Debrecen - Ujhelyi, Mária; Kun, András István (International Journal of Engineering and Management Sciences, 2016)
Based on the OCAI model, our study analyses and compares two things (1) the corporate culture of the University of Debrecen Faculty of Engineering as it is perceived by its engineering management students; and (2) the culture they think would be ideal. According to the respondents the existing culture is closer to the clan type and further from the market type compared to the average. Their ideal culture is closer to the clan, adhocracy and further from the market (compared to the average). The perceived current and the ideal culture are significantly different only in the adhocracy type. From the 20 items of the OCAI questionnaire 7 were significantly different from the average in the case of the perceived culture and 13 in the case of the ideal culture. Differences between ideal and present cultures are statistically supported only in the following dimensions: dominant characteristics (clan is currently stronger, adhocracy is weaker), corporate leadership (market is currently stronger), strategic emphasis (hierarchy is currently stronger).